Foundations of mathematical analysis - Johnsonbaugh, R Richard Johnsonbaugh; Pfaffenberger, W.E W.E. Pfaffenberger (New York: Dover Publication, 2002)
This classroom-tested volume offers a definitive look at modern analysis, with views of applications to statistics, numerical analysis, Fourier series, differential equations, mathematical analysis, and functional analysis. Upper-level undergraduate students with a background in calculus will benefit from its teachings, along with beginning graduate students seeking a firm grounding in modern analysis.
Includes appendix and index
Keywords: Mathematics